Implementasi Metode Fuzzy Tsukamoto Untuk Memprediksi Besarnya Pemakaian Listrik Rumah Tangga - Tempola, Firman; Sujabtri Kabau, Haan; Fuad, Achmad; Rosihan; Lutfi, Salkin (Computer Science and Information Technology, 2024)
Many people are still confused about ordering the voltage level for electricity use in newly built homes, so that for households that previously needed a voltage of 900 VA, it was sufficient but used 1300 VA and vice versa, if the use of a large voltage of 900 VA is not in accordance with the number of customers' needs, then there will be a disturbance in the balance between the amount of voltage used and customer needs, but by applying the fuzzy method this can be predicted. The aim of this research is to predict the voltage of household electricity usage using the fuzzy Tsukamoto method. This method was chosen because it is flexible, and has tolerance for existing data and also has the advantages of being faster in computing, more intuitive, and also produces accurate prediction values. The results of implementing the fuzzy Tsukamoto method were tested for accuracy using the Mean Absolute Percentage Error (MAPE) method. The first test used 20 data as test data and the second test used 30 test data, so that the results obtained from the first test were 8.35% and the second test was 11.77%. Based on the table of capability values of the MAPE method forecasting model, the results of implementing the fuzzy Tsukamoto method can be used to predict the amount of household electricity usage with a percentage value < 20%, which is a good forecasting model capability.